Preparation method and application of nano flower ball Ov-(Ni0. 5Co0. 5) V2O8 / P-coated CNT composite film electrode material

By preparing nanoflower ball Ov-(Ni0.5Co0.5)V2O8/P@CNT composite film electrode material, the irreversible attenuation problem caused by ion insertion/deintercalation during the charge and discharge cycle of existing electrode materials is solved, and the problem of irreversible attenuation caused by ion insertion/deintercalation during the charge and discharge cycle is achieved. Supercapacitor electrode material with high energy density and power density.

CN119517636APending Publication Date: 2025-02-25JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411650843.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing supercapacitor electrode materials have volume expansion due to ion insertion/deintercalation during the charge and discharge cycle, resulting in irreversible attenuation of the capacitor, and the slow reaction kinetics and limited electroactive sites, limiting their energy density and conductivity.

Method used

The preparation method of nanoflower sphere Ov-(Ni0.5Co0.5)V2O8/P@CNT composite thin film electrode material is adopted, and carbon nanotubes and transition metal oxidation is combined with carbon nanotubes and transition metal oxidation through rapid chemical reaction method, oil bath method and high-temperature phosphating method. to form a composite material with high conductivity and high specific surface area.

Benefits of technology

It significantly improves the conductivity and specific surface area of ​​the electrode material, increases the reactive site, improves the cyclic stability and electrochemical performance of the material, and improves the energy density and power density of the supercapacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517636A_ABST
    Figure CN119517636A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite electrode materials, and relates to a preparation method of a nano flower ball Ov-(Ni0. 5Co0. 5) V2O8 / P (at) CNT composite film electrode material, which comprises the following steps: uniformly mixing and stirring a cobalt salt-CNT methanol solution and a 2-methylimidazole methanol solution in equal volume, and carrying out suction filtration to obtain a ZIF-67 (at) CNT film; then immersing in a solution prepared from nickel salt, K2S2O8, ammonia water and deionized water to obtain a NiCo-LDH-coated CNT film; then immersing the CNT film into a solution prepared from NH4VO3, ammonia water and deionized water to obtain a (Ni0. 5Co0. 5) 3V2O8 coated CNT composite film; and finally, carrying out high-temperature phosphorization. The prepared composite material is also applied to a supercapacitor electrode. The carbon nano tube provides a flexible substrate for the self-supporting material, the conductivity and the specific surface area of the material are greatly increased, meanwhile, (Ni0. 5Co0. 5) V2O8 directly grows on the carbon nano tube in situ, the use of an adhesive is avoided, the impedance of the material is reduced, and in addition, the doping of P also provides a large number of reactive active sites for the electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode materials, and relates to composite electrode materials, in particular to a nano flower ball Ov-(Ni 0.5 Co 0.5 )Preparation method and application of V2O8 / P@CNT composite thin film electrode material. Background Art

[0002] Due to the rapid economic development, the energy crisis is getting worse and worse, and there is an urgent need to find green energy storage devices to store and utilize new energy. Supercapacitors have attracted much attention as promising energy storage devices. One of the main challenges they face is how to improve energy density, which is closely related to the energy storage capacity of electrode materials. Therefore, the rational design of electrode materials is the key to improving the energy density of supercapacitor electrode materials. Carbon-based materials such as carbon nanotubes (CNTs), carbon cloth (CC), and graphene have been widely studied as substrates for self-supporting electrodes. One-dimensional carbon nanotubes have high conductivity and large specific surface area. They are cross-linked to form a network structure, which provides abundant channels for the efficient transfer of electrons and ions. Moreover, combining carbon nanotubes with metal oxides, hydroxides, etc. can greatly improve the conductivity of electrode materials.

[0003] Transition metal oxides (TMOs) are widely used in the field of supercapacitors due to their diverse oxidation states and excellent electrical conductivity. TMOs accumulate charge through electrostatics and store energy through Faraday redox reactions, thereby improving the energy density of supercapacitors. Compared with single metal oxides, ternary metal oxides with multiple oxidation states are recognized as pseudocapacitive materials and have been well developed as supercapacitor electrodes. However, due to the volume expansion of TMOs caused by the insertion / deintercalation of ions during the charge and discharge cycle of the device, the capacitance is partially irreversibly attenuated. In addition, its inherent slow reaction kinetics and limited electroactive sites result in low ionic and electronic conductivity and low actual capacity. Recent studies have shown that defect engineering by introducing heteroatoms into metal oxides can provide additional redox reaction active sites and surface reactivity, thereby improving the capacity and energy density of the material.

[0004] Doping can significantly improve the surface reaction and overall performance of electrode materials. The appropriate amount of heteroatoms or functional groups introduced can change the structure and performance of the material. First, heteroatom doping can cause the expansion of crystal cells, which not only expands the ion transfer pathway, but also expands the storage space; secondly, the introduction of heteroatoms can promote the redistribution of internal charges in electrode materials, especially distorting the charges of surface atoms, thereby improving the conductivity of the material. Therefore, heteroatom doping carefully regulates the intrinsic crystal structure of active materials, affects the charge state, band gap, ion diffusion coefficient and crystal structure stability of active materials, and ultimately obtains better electrochemical performance. Summary of the invention

[0005] In order to overcome the defects of the prior art, one object of the present invention is to disclose a nano flower ball Ov-(Ni 0.5 Co 0.5 )Preparation method of V2O8 / P@CNT composite thin film electrode material.

[0006] Technical Solution

[0007] Using cobalt salt, 2-methylimidazole (C4H6N2), nickel salt, ammonium vanadate (NH4VO3), potassium persulfate (K2S2O8), ammonia (NH3·H2O), sodium hypophosphite (NaH2PO2) and carbon nanotubes (CNT) as raw materials, ZIF-67@CNT material was first obtained by a rapid chemical reaction method, and then (Ni 0.5 Co 0.5 )V2O8@CNT, and finally Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite thin film electrode material.

[0008] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0009] A. Mix equal volumes of cobalt salt-CNT methanol solution and 2-methylimidazole methanol solution, stir evenly, let stand for 12 to 24 hours, preferably 24 hours, then vacuum filter, and dry at 60° C. to obtain a ZIF-67@CNT film;

[0010] Wherein, in the cobalt salt-CNT methanol solution, the material ratio of cobalt salt: CNT: methanol is 2-4 mmol:

[0011] 0.5~1.2mL:15~25mL; the cobalt salt is Co(NO3)2 or CoCl2; in the 2-methylimidazole methanol solution, the material ratio of 2-methylimidazole:methanol is 0.820~2.460g:15~25mL;

[0012] B. According to the material ratio of nickel salt: K2S2O8: ammonia water: deionized water, the material ratio is 6-12mmol: 0.270-0.811

[0013] g: 0.5~2mL: 20~50mL of prepared solution was immersed in the above ZIF-67@CNT film for 0.5~1

[0014] h, preferably 0.5h, take it out, wash it with deionized water and anhydrous ethanol, and dry it at 60°C to obtain NiCo-

[0015] LDH@CNT film, wherein the nickel salt is NiSO4 or NiCl2;

[0016] C. According to the ratio of NH4VO3: ammonia water: deionized water: 0.06-0.117g: 0.5-2mL: 13-24.5

[0017] mL was prepared into a solution, and ultrasonically homogenized; the NiCo-LDH@CNT film was immersed in it, and the solution was bathed in oil at 50-80°C for 30 min, preferably at 80°C for 30 min, and then taken out, washed with deionized water and anhydrous ethanol, and dried at 60°C to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT composite film;

[0018] D. Prepared (Ni 0.5 Co 0.5 The 3V2O8@CNT composite membrane and NaH2PO2·H2O were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace in a nitrogen atmosphere at 2-5℃·min -1 The temperature is raised at a heating rate of 300-350°C for 1-2h, preferably at a heating rate of 2°C·min -1 The temperature was raised at a heating rate of 350 ° C for 2 h to obtain Ov-

[0019] (Ni 0.5 Co 0.5 )V2O8 / P@CNT composite thin film electrode material.

[0020] According to a preferred disclosed example of the present invention, in step A, in the cobalt salt-CNT methanol solution, the material ratio of cobalt salt:CNT:methanol is 3mmol:0.8mL:20mL.

[0021] According to a preferred disclosed example of the present invention, in step A, in the 2-methylimidazole methanol solution, the material ratio of 2-methylimidazole:methanol is 1.633 g:20 mL.

[0022] According to a preferred embodiment of the present invention, in step B, the material ratio of nickel salt: K2S2O8: ammonia water: deionized water is 9.5 mmol: 0.514 g: 1.250 mL: 25 mL.

[0023] In a preferred embodiment of the present invention, in steps B and C, the concentration of the ammonia water is 28%.

[0024] According to a preferred embodiment of the present invention, in step C, the ratio of NH4VO3: ammonia water: deionized water is 0.09 g: 1 mL: 19 mL.

[0025] The Ov-(Ni 0.5 Co 0.5 )The size of the V2O8 / P@CNT composite film electrode material can be cut at will according to the actual situation. Under the microscopic state, it can be observed that a large number of nano flower balls are loaded on the surface of the carbon tube.

[0026] Another object of the present invention is to prepare the Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite thin film electrode material as supercapacitor electrode.

[0027] The prepared Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film electrode material was used as the positive electrode, and 6 molL -1 The activated carbon, conductive carbon black and binder were uniformly mixed and dispersed in N-methylpyrrolidone solution in a mass ratio of 8:1:1, and then coated on nickel foam, dried and pressed to prepare electrode sheets as the negative electrode material of the capacitor. The electrochemical performance tests such as cyclic voltammetry (CV) and constant current charge and discharge (GCD) were carried out in a two-electrode system, and the corresponding energy density and power density were calculated to evaluate the prepared Ov-(Ni 0.5 Co 0.5 )Electrochemical properties of V2O8 / P@CNT composite film electrode materials. The voltage range of the cyclic voltammetry (CV) test was 0-0.5V, and the scan rates were 2, 5, 10, 20, 50 and 100 mV s -1 The voltage range of the constant current charge and discharge test is 0-0.5V, and the current density is 1, 2, 3, 5, 8 and 10Ag. -1 .

[0028] The Ov-(Ni 0.5Co 0.5 )V2O8 / P@CNT composite thin film electrode material was analyzed by field emission scanning electron microscopy (SEM), X-ray diffractometer (XRD), CHI760E electrochemical workstation and other instruments to evaluate its electrochemical activity.

[0029] Carbon nanotubes have many advantages such as good electrical conductivity, stable thermodynamic and chemical properties, and can be easily formed into thin films as a self-supporting substrate to form an interconnected conductive porous network structure.

[0030] The reactants and reagents used in the present invention are all commercially available.

[0031] Beneficial Effects

[0032] The present invention synthesizes Ov-(Ni) by three steps of simple chemical reaction method, oil bath method and subsequent high temperature phosphating method. 0.5 Co 0.5 )V2O8 / P@CNT composite film electrode material. Carbon nanotubes provide a flexible substrate for self-supporting materials, greatly increasing the conductivity and specific surface area of ​​the material. 0.5 Co 0.5 )V2O8 grows directly on carbon nanotubes in situ, avoiding the use of adhesives and reducing the impedance of the material. In addition, P doping also provides a large number of active sites for the reaction of the electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 . Ov-(Ni prepared in Example 1 0.5 Co 0.5 )Scanning electron microscope image of V2O8 / P@CNT composite thin film electrode material;

[0034] Figure 2 Example 1 Preparation of Ov-(Ni 0.5 Co 0.5 ) XRD curve of V2O8 / P@CNT composite thin film electrode material;

[0035] Figure 3 Example 1 Preparation of Ov-(Ni 0.5 Co 0.5 )GCD curve of V2O8 / P@CNT composite thin film electrode material;

[0036] Figure 4 Example 1 Preparation of Ov-(Ni 0.5 Co 0.5 )Energy density-power density diagram of supercapacitors assembled with V2O8 / P@CNT composite thin film electrode materials;

[0037] Figure 5Example 1 Preparation of Ov-(Ni 0.5 Co 0.5 ) Cyclic stability diagram of supercapacitor assembled with V2O8 / P@CNT composite thin film electrode material. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with the embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.

[0039] Unless otherwise defined, the terms (including technical terms) used herein should be interpreted as having the same meaning as commonly understood by those skilled in the art to which the present invention belongs. It will also be understood that the terms used herein should be interpreted as having the meaning consistent with their meanings in the content of this specification and related technologies, and should not be interpreted in an idealized or excessive form unless specifically defined as such herein.

[0040] Example 1

[0041] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0042] Step 1, weigh 3mmol Co(NO3)2·6H2O and 0.8mL CNT, dissolve them in 20mL methanol; weigh 1.633g 2-methylimidazole, dissolve them in 20mL methanol, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 24 hours, vacuum filter them, and dry them at 60°C to obtain a ZIF-67@CNT film;

[0043] Step 2: Weigh 9.5mmol NiSO4, 0.514g K2S2O8 and 1.250mL ammonia (28%) and dissolve them in 25mL deionized water. Immerse the prepared ZIF-67@CNT film in the above solution and soak it at room temperature for half an hour. Take out the sample after half an hour, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCo-LDH@CNT film;

[0044] Step 3, weigh 0.090g NH4VO3 and dissolve it in 1mL ammonia water (28%) and 19mL deionized water solution, and after ultrasonication for 20min, immerse the NiCo-LDH@CNT film in an oil bath at 80℃ for 30min, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT;

[0045] Step 4: Prepare (Ni 0.5 Co 0.5 )3V2O8@CNT composite film and NaH2PO2·H2O (mass ratio of 1:5) were heated at 2℃·min in nitrogen atmosphere. -1 The heating rate was calcined at 350 ° C for 2 hours to obtain Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film.

[0046] Ov-(Ni 0.5 Co 0.5 )Characterization and analysis of V2O8 / P@CNT composite film electrode materials

[0047] like Figure 1 As shown in the figure, it can be seen that in the microscopic state, Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite material presents nano-flower ball shape, interlaced with carbon nanotubes to form a network structure with ultra-high specific surface area.

[0048] like Figure 2 As shown, it is Ov-(Ni 0.5 Co 0.5 )XRD test results of V2O8 / P@CNT composite materials.

[0049] like Figure 3 As shown in the figure, it can be seen that Ov-(Ni 0.5 Co 0.5 )GCD curve of V2O8 / P@CNT composite material. It can be calculated that the material has a current density of 1A·g -1 1477.6F·g -1 High specific capacity.

[0050] like Figure 4 As shown, the Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite material is used as supercapacitor electrode material in two-electrode system. From the energy density-power density diagram, it can be seen that the assembled supercapacitor has good power density and energy density. When the maximum energy density reaches 127.5Wh·kg -1 Its power density is 800W·kg -1 .

[0051] like Figure 5 As shown, the Ov-(Ni 0.5 Co 0.5)The results of the cycle stability test of V2O8 / P@CNT activated carbon composite material used as electrode material showed that its specific capacitance returned to the initial capacity after 10,000 cycles, with a capacity retention rate of 100%, showing good cycle performance.

[0052] Example 2

[0053] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0054] Step 1, weigh 3mmol CoCl2·6H2O and 0.8mL CNT, dissolve them in 20mL methanol; weigh 1.633g 2-methylimidazole, dissolve them in 20mL methanol, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 24 hours, vacuum filter them, and dry them at 60°C to obtain a ZIF-67@CNT film;

[0055] Step 2: Weigh 9.5mmol NiSO4, 0.514g K2S2O8 and 1.250mL ammonia (28%) and dissolve them in 25mL deionized water. Immerse the prepared ZIF-67@CNT film in the above solution and soak it at room temperature for half an hour. Take out the sample after half an hour, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCo-LDH@CNT film;

[0056] Step 3, weigh 0.090g NH4VO3 and dissolve it in 1mL ammonia water (28%) and 19mL deionized water solution, and after ultrasonication for 20min, immerse the NiCo-LDH@CNT film in an oil bath at 80℃ for 30min, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT;

[0057] Step 4: Prepare (Ni 0.5 Co 0.5 )3V2O8@CNT composite film and NaH2PO2·H2O (mass ratio of 1:5) were heated at 2℃·min in nitrogen atmosphere. -1 The heating rate was calcined at 350 ° C for 2 hours to obtain Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film.

[0058] The Ov-(Ni 0.5 Co 0.5) When V2O8 / P@CNT / / activated carbon composite material is used as electrode material, the maximum energy density reaches 124.6Wh·kg -1 Its power density is 800W·kg -1 .

[0059] Example 3

[0060] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0061] Step 1, weigh 3mmol Co(NO3)2·6H2O and 0.8mL CNT, dissolve them in 20mL methanol; weigh 1.633g 2-methylimidazole, dissolve them in 20mL methanol, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 24 hours, vacuum filter them, and dry them at 60°C to obtain a ZIF-67@CNT film;

[0062] Step 2: Weigh 9.5mmol NiCl2, 0.514g K2S2O8 and 1.250mL ammonia (28%) and dissolve them in 25mL deionized water. Immerse the prepared ZIF-67@CNT film in the above solution and soak it at room temperature for half an hour. Take out the sample after half an hour, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCo-LDH@CNT film;

[0063] Step 3, weigh 0.090g NH4VO3 and dissolve it in 1mL ammonia water (28%) and 19mL deionized water solution, and after ultrasonication for 20min, immerse the NiCo-LDH@CNT film in an oil bath at 80℃ for 30min, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT;

[0064] Step 4: Prepare (Ni 0.5 Co 0.5 )3V2O8@CNT composite film and NaH2PO2·H2O (mass ratio of 1:5) were heated at 2℃·min in nitrogen atmosphere. -1 The heating rate was calcined at 350 ° C for 2 hours to obtain Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film.

[0065] The Ov-(Ni 0.5 Co 0.5) When V2O8 / P@CNT / / activated carbon composite material is used as electrode material, the maximum energy density reaches 122.9Wh·kg -1 Its power density is 800W·kg -1 .

[0066] Example 4

[0067] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0068] Step 1, weigh 3mmol Co(NO3)2·6H2O and 0.8mL CNT, dissolve them in 20mL methanol; weigh 1.633g 2-methylimidazole, dissolve them in 20mL methanol, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 12 hours, vacuum filter them, and dry them at 60°C to obtain a ZIF-67@CNT film;

[0069] Step 2: Weigh 9.5mmol NiSO4, 0.514g K2S2O8 and 1.250mL ammonia (28%) and dissolve them in 25mL deionized water. Immerse the prepared ZIF-67@CNT film in the above solution and soak it at room temperature for half an hour. Take out the sample after half an hour, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCo-LDH@CNT film;

[0070] Step 3, weigh 0.090g NH4VO3 and dissolve it in 1mL ammonia water (28%) and 19mL deionized water solution, and after ultrasonication for 20min, immerse the NiCo-LDH@CNT film in an oil bath at 80℃ for 30min, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT;

[0071] Step 4: Prepare (Ni 0.5 Co 0.5 )3V2O8@CNT composite film and NaH2PO2·H2O (mass ratio of 1:5) were heated at 2℃·min in nitrogen atmosphere. -1 The heating rate was calcined at 350 ° C for 2 hours to obtain Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film.

[0072] The Ov-(Ni 0.5 Co 0.5) When V2O8 / P@CNT / / activated carbon composite material is used as electrode material, the maximum energy density reaches 117.3Wh·kg -1 Its power density is 800W·kg -1 .

[0073] Example 5

[0074] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0075] Step 1, weigh 4mmol Co(NO3)2·6H2O and 1.2mL CNT, dissolve them in 25mL methanol; weigh 2.46g 2-methylimidazole, dissolve them in 25mL methanol, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 24 hours, vacuum filter them, and dry them at 60°C to obtain a ZIF-67@CNT film;

[0076] Step 2: Weigh 12mmol NiSO4, 0.811g K2S2O8 and 2.00mL ammonia (28%) and dissolve them in 20mL deionized water. Immerse the prepared ZIF-67@CNT film in the above solution and soak it at room temperature for half an hour. Take out the sample after half an hour, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCo-LDH@CNT film;

[0077] Step 3, weigh 0.117g NH4VO3 and dissolve it in 2mL ammonia water (28%) and 13mL deionized water solution, and after ultrasonication for 20min, immerse the NiCo-LDH@CNT film in an oil bath at 80℃ for 30min, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT;

[0078] Step 4: Prepare (Ni 0.5 Co 0.5 )3V2O8@CNT composite film and NaH2PO2·H2O (mass ratio of 1:5) were heated at 2℃·min in nitrogen atmosphere. -1 The heating rate was calcined at 350 ° C for 2 hours to obtain Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film.

[0079] The Ov-(Ni 0.5 Co 0.5) When V2O8 / P@CNT / / activated carbon composite material is used as electrode material, the maximum energy density reaches 120.5Wh·kg -1 Its power density is 800W·kg -1 .

[0080] Example 6

[0081] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0082] Step 1, weigh 2mmol Co(NO3)2·6H2O and 0.5mL CNT, dissolve them in 15mL methanol; weigh 0.821g 2-methylimidazole, dissolve them in 15mL methanol, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 24 hours, vacuum filter them, and dry them at 60°C to obtain a ZIF-67@CNT film;

[0083] Step 2: Weigh 6mmol NiSO4, 0.270g K2S2O8 and 0.50mL ammonia (28%) and dissolve them in 50mL deionized water. Immerse the prepared ZIF-67@CNT film in the above solution and soak it at room temperature for half an hour. Take out the sample after half an hour, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCo-LDH@CNT film;

[0084] Step 3, weigh 0.06g NH4VO3 and dissolve it in 0.5mL ammonia water (28%) and 24.5mL deionized water solution, and after ultrasonication for 20min, immerse the NiCo-LDH@CNT film in an oil bath at 80℃ for 30min, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT;

[0085] Step 4: Prepare (Ni 0.5 Co 0.5 )3V2O8@CNT composite film and NaH2PO2·H2O (mass ratio of 1:5) were heated at 2℃·min in nitrogen atmosphere. -1 The heating rate was calcined at 350 ° C for 2 hours to obtain Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film.

[0086] The Ov-(Ni 0.5 Co 0.5) When V2O8 / P@CNT / / activated carbon composite material is used as electrode material, the maximum energy density reaches 95.1Wh·kg -1 Its power density is 800W·kg -1 .

[0087] Example 7

[0088] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0089] Step 1, weigh 3mmol Co(NO3)2·6H2O and 0.8mL CNT, dissolve them in 20mL methanol; weigh 1.633g 2-methylimidazole, dissolve them in 20mL methanol, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 24 hours, vacuum filter them, and dry them at 60°C to obtain a ZIF-67@CNT film;

[0090] Step 2: Weigh 9.5mmol NiSO4, 0.514g K2S2O8 and 1.250mL ammonia (28%) and dissolve them in 25mL deionized water. Immerse the prepared ZIF-67@CNT film in the above solution and soak it at room temperature for 1 hour. After 1 hour, take out the sample, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCo-LDH@CNT film;

[0091] Step 3, weigh 0.090g NH4VO3 and dissolve it in 1mL ammonia water (28%) and 19mL deionized water solution, and after ultrasonication for 20min, immerse the NiCo-LDH@CNT film in an oil bath at 80℃ for 30min, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT;

[0092] Step 4: Prepare (Ni 0.5 Co 0.5 )3V2O8@CNT composite film and NaH2PO2·H2O (mass ratio of 1:5) were heated at 2℃·min in nitrogen atmosphere. -1 The heating rate was calcined at 350 ° C for 2 hours to obtain Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film.

[0093] The Ov-(Ni 0.5 Co 0.5) When V2O8 / P@CNT / / activated carbon composite material is used as electrode material, the maximum energy density reaches 121.5Wh·kg -1 Its power density is 800W·kg -1 .

[0094] Example 8

[0095] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0096] Step 1, weigh 3mmol Co(NO3)2·6H2O and 0.8mL CNT, dissolve them in 20mL methanol; weigh 1.633g 2-methylimidazole, dissolve them in 20mL methanol, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 24 hours, vacuum filter them, and dry them at 60°C to obtain a ZIF-67@CNT film;

[0097] Step 2: Weigh 9.5mmol NiSO4, 0.514g K2S2O8 and 1.250mL ammonia (28%) and dissolve them in 25mL deionized water. Immerse the prepared ZIF-67@CNT film in the above solution and soak it at room temperature for half an hour. Take out the sample after half an hour, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCo-LDH@CNT film;

[0098] Step 3, weigh 0.090g NH4VO3 and dissolve it in 1mL ammonia water (28%) and 19mL deionized water solution, and after ultrasonication for 20min, immerse the NiCo-LDH@CNT film in an oil bath at 50℃ for 30min, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT;

[0099] Step 4: Prepare (Ni 0.5 Co 0.5 )3V2O8@CNT composite film and NaH2PO2·H2O (mass ratio of 1:5) were heated at 2℃·min in nitrogen atmosphere. -1 The heating rate was calcined at 350 ° C for 2 hours to obtain Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film.

[0100] The Ov-(Ni 0.5 Co 0.5) When V2O8 / P@CNT / / activated carbon composite material is used as electrode material, the maximum energy density reaches 80.3Wh·kg -1 Its power density is 800W·kg -1 .

[0101] Example 9

[0102] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0103] Step 1, weigh 3mmol Co(NO3)2·6H2O and 0.8mL CNT, dissolve them in 20mL methanol; weigh 1.633g 2-methylimidazole, dissolve them in 20mL methanol, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 24 hours, vacuum filter them, and dry them at 60°C to obtain a ZIF-67@CNT film;

[0104] Step 2: Weigh 9.5mmol NiSO4, 0.514g K2S2O8 and 1.250mL ammonia (28%) and dissolve them in 25mL deionized water. Immerse the prepared ZIF-67@CNT film in the above solution and soak it at room temperature for half an hour. Take out the sample after half an hour, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCo-LDH@CNT film;

[0105] Step 3, weigh 0.090g NH4VO3 and dissolve it in 1mL ammonia water (28%) and 19mL deionized water solution, and after ultrasonication for 20min, immerse the NiCo-LDH@CNT film in an oil bath at 80℃ for 30min, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT;

[0106] Step 4: Prepare (Ni 0.5 Co 0.5 )3V2O8@CNT composite film and NaH2PO2·H2O (mass ratio of 1:2) were heated at 2℃·min in nitrogen atmosphere. -1 The heating rate was calcined at 350 ° C for 2 hours to obtain Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film.

[0107] The Ov-(Ni 0.5 Co 0.5) When V2O8 / P@CNT / / activated carbon composite material is used as electrode material, the maximum energy density reaches 93.1Wh·kg -1 Its power density is 800W·kg -1 .

[0108] Example 10

[0109] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0110] Step 1, weigh 3mmol Co(NO3)2·6H2O and 0.8mL CNT, dissolve them in 20mL methanol; weigh 1.633g 2-methylimidazole, dissolve them in 20mL methanol, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 24 hours, vacuum filter them, and dry them at 60°C to obtain a ZIF-67@CNT film;

[0111] Step 2: Weigh 9.5mmol NiSO4, 0.514g K2S2O8 and 1.250mL ammonia (28%) and dissolve them in 25mL deionized water. Immerse the prepared ZIF-67@CNT film in the above solution and soak it at room temperature for half an hour. Take out the sample after half an hour, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCo-LDH@CNT film;

[0112] Step 3, weigh 0.090g NH4VO3 and dissolve it in 1mL ammonia water (28%) and 19mL deionized water solution, and after ultrasonication for 20min, immerse the NiCo-LDH@CNT film in an oil bath at 80℃ for 30min, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT;

[0113] Step 4: Prepare (Ni 0.5 Co 0.5 )3V2O8@CNT composite film and NaH2PO2·H2O (mass ratio of 1:5) were heated at 5℃·min in nitrogen atmosphere. -1 The heating rate was calcined at 350 ° C for 2 hours to obtain Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film.

[0114] The Ov-(Ni 0.5 Co 0.5) When V2O8 / P@CNT / / activated carbon composite material is used as electrode material, the maximum energy density reaches 125.4Wh·kg -1 Its power density is 800W·kg -1 .

[0115] Embodiment 11

[0116] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0117] Step 1, weigh 3mmol Co(NO3)2·6H2O and 0.8mL CNT, dissolve them in 20mL methanol; weigh 1.633g 2-methylimidazole, dissolve them in 20mL methanol, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 24 hours, vacuum filter them, and dry them at 60°C to obtain a ZIF-67@CNT film;

[0118] Step 2: Weigh 9.5mmol NiSO4, 0.514g K2S2O8 and 1.250mL ammonia (28%) and dissolve them in 25mL deionized water. Immerse the prepared ZIF-67@CNT film in the above solution and soak it at room temperature for half an hour. Take out the sample after half an hour, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCo-LDH@CNT film;

[0119] Step 3, weigh 0.090g NH4VO3 and dissolve it in 1mL ammonia water (28%) and 19mL deionized water solution, and after ultrasonication for 20min, immerse the NiCo-LDH@CNT film in an oil bath at 80℃ for 30min, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT;

[0120] Step 4: Prepare (Ni 0.5 Co 0.5 )3V2O8@CNT composite film and NaH2PO2·H2O (mass ratio of 1:5) were heated at 2℃·min in nitrogen atmosphere. -1 The heating rate was calcined at 300 °C for 2 hours to obtain Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film.

[0121] The Ov-(Ni 0.5 Co 0.5) When V2O8 / P@CNT / / activated carbon composite material is used as electrode material, the maximum energy density reaches 96.3Wh·kg -1 Its power density is 800W·kg -1 .

[0122] Example 12

[0123] A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, comprising the following steps:

[0124] Step 1, weigh 3mmol Co(NO3)2·6H2O and 0.8mL CNT, dissolve them in 20mL methanol; weigh 1.633g 2-methylimidazole, dissolve them in 20mL methanol, mix the Co(NO3)2 methanol solution and the 2-methylimidazole solution and stir for 10 minutes, place them at room temperature for 24 hours, vacuum filter them, and dry them at 60°C to obtain a ZIF-67@CNT film;

[0125] Step 2: Weigh 9.5mmol NiSO4, 0.514g K2S2O8 and 1.250mL ammonia (28%) and dissolve them in 25mL deionized water. Immerse the prepared ZIF-67@CNT film in the above solution and soak it at room temperature for half an hour. Take out the sample after half an hour, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C to obtain NiCo-LDH@CNT film;

[0126] Step 3, weigh 0.090g NH4VO3 and dissolve it in 1mL ammonia water (28%) and 19mL deionized water solution, and after ultrasonication for 20min, immerse the NiCo-LDH@CNT film in an oil bath at 80℃ for 30min, take out the sample, wash the sample with deionized water and anhydrous ethanol several times, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT;

[0127] Step 4: Prepare (Ni 0.5 Co 0.5 )3V2O8@CNT composite film and NaH2PO2·H2O (mass ratio of 1:5) were heated at 2℃·min in nitrogen atmosphere. -1 The heating rate was calcined at 350℃ for 1 hour to obtain Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite film.

[0128] The Ov-(Ni 0.5 Co 0.5) When V2O8 / P@CNT / / activated carbon composite material is used as electrode material, the maximum energy density reaches 90.2Wh·kg -1 Its power density is 800W·kg -1 .

[0129] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A nano flower ball Ov-(Ni 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, characterized in that: The following steps are involved: A. Mix equal volumes of cobalt salt-CNT methanol solution and 2-methylimidazole methanol solution, stir evenly, let stand for 12-24 hours, vacuum filter, and dry at 60°C to obtain a ZIF-67@CNT film; wherein, in the cobalt salt-CNT methanol solution, the material ratio of cobalt salt: CNT: methanol is 2-4mmol: 0.5-1.2mL: 15-25mL; the cobalt salt is Co(NO3)2 or CoCl2; in the 2-methylimidazole methanol solution, the material ratio of 2-methylimidazole: methanol is 0.820-2.460g: 15-25mL; B. Prepare a solution according to the material ratio of nickel salt: K2S2O8: ammonia water: deionized water of 6~12 mmol: 0.270~0.811 g: 0.5~2 mL: 20~50 mL, immerse the above ZIF-67@CNT film, soak for 0.5~1h, take out, wash with deionized water and anhydrous ethanol, and dry at 60°C to obtain a NiCo-LDH@CNT film, wherein the nickel salt is NiSO4 or NiCl2; C. Prepare a solution according to the ratio of NH4VO3: ammonia water: deionized water of 0.06~0.117g: 0.5~2mL: 13~24.5mL, and ultrasonically homogenize; immerse the above NiCo-LDH@CNT film in it, and bathe it in oil at 50~80℃ for 30min, preferably at 80℃ for 30min, take it out, wash it with deionized water and anhydrous ethanol, and dry it at 60℃ to obtain (Ni 0.5 Co 0.5 )3V2O8@CNT composite film; D. Prepared (Ni 0.5 Co 0.5 The 3V2O8@CNT composite membrane and NaH2PO2·H2O were placed in two separate porcelain boats at the upstream and downstream ends of the tube furnace in a nitrogen atmosphere at 2~5℃·min -1 The temperature is raised at a heating rate of 300-350°C for 1-2 h, preferably at a heating rate of 2°C·min -1 The temperature is raised at a heating rate of and calcined at 350°C for 2h to obtain the product.

2. The nano flower ball Ov-(Ni according to claim 1 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, characterized in that: In step A, the cobalt salt-CNT methanol solution and the 2-methylimidazole methanol solution were mixed and stirred in equal volumes, allowed to stand for 24 h, and then vacuum filtered and dried at 60° C. to obtain a ZIF-67@CNT film.

3. The nano flower ball Ov-(Ni according to claim 1 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, characterized in that: In step A, in the cobalt salt-CNT methanol solution, the material ratio of cobalt salt: CNT: methanol is 3mmol: 0.8mL: 20mL.

4. The nano flower ball Ov-(Ni according to claim 1 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, characterized in that: In step A, in the 2-methylimidazole methanol solution, the material ratio of 2-methylimidazole: methanol is 1.633 g: 20 mL.

5. The nano flower ball Ov-(Ni according to claim 1 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, characterized in that: In step B, the material ratio of the nickel salt: K2S2O8: ammonia water: deionized water is 9.5 mmol: 0.514 g: 1.250 mL: 25 mL.

6. The nano flower ball Ov-(Ni according to claim 1 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, characterized in that: In step B, the ZIF-67@CNT film is immersed in the above-mentioned film for 0.5 h and then taken out.

7. The nano flower ball Ov-(Ni according to claim 1 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, characterized in that: In steps B and C, the concentration of the aqueous ammonia is 28%.

8. The nano flower ball Ov-(Ni according to claim 1 0.5 Co 0.5 ) A method for preparing a V2O8 / P@CNT composite thin film electrode material, characterized in that: In step C, the ratio of NH4VO3: ammonia water: deionized water is 0.09 g: 1 mL: 19 mL.

9. The nano flower ball Ov-(Ni 0.5 Co 0.5 )V2O8 / P@CNT composite thin film electrode material, characterized in that: The microscopic morphology shows that a large number of nano-flower balls are loaded on the surface of carbon tubes.

10. A nano flower ball Ov-(Ni 0.5 Co 0.5 ) Application of V2O8 / P@CNT composite thin film electrode material, characterized by: It is applied to supercapacitor electrodes.